Diseño de un manual de buenas prácticas de manufactura (BPM) para la empresa ACUA VID en el municipio de GRANADA – META - Fernandez Barras, Leidy Lauren; Peña Ramírez, Yajaira Tatiana (Universidad Antonio Nariño, 2021)
The purpose of this project is to design a manual of good manufacturing practices (BPM) for the company ACUA VID in the municipality of Granada-Meta and to achieve this, a diagnosis was applied that allows us to assess the strengths and weaknesses in the matter of the program BPM Which will have access to the company to comply with the established norms that currently regulate food processing plants. At the time of identifying in the diagnosis carried out sanitary non-compliances within the production process, the company ACUA VID should be proposed corrective and preventive actions that contribute to the development of safe and innocuous practices within the organization and then document to the company the Good System Manufacturing practices through a didactic manual taking into account the findings found from the diagnosis, partial non-compliance and applicable regulations for the modification of its relevance and subsequent application and also to publicize the System of Good Manufacturing Practices through training to the entire staff to promote its applicability within the organization. It is important to identify our project is focused on complying with the BPM standards, that is why it is necessary to carry out different background studies in our country and in different parts of the world to identify the viability of the BPM program in the different sectors and also analyze projects. similar to meet the stated objectives